Solutions to the Problem of the Dichotomy of Knowledge in Islamic Higher Education (An Analysis of Higher Education Policy) - Muqit, Abdul; Abidin, Zainal; Mustaqim, Mustaqim (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2021)
This study seeks to explore the problem of the dichotomy of science and its solution in Islamic Higher Education. which is analyzed in the perspective of education policy regarding higher education regulations by using the content analysis method in the study of library research. The issue of the dichotomy of science is actually a classic issue of the dark legacy of the past colonialism which Indonesia's founding fathers have been fighting for a long time. This real effort is proven by the issuance of a joint decree initiated by the Minister of Religion, KH. Wahid Hasyim and the Minister of Education of the Republic of Indonesia regarding the implementation of religious teaching in state educational institutions which are stipulated through the Regulation of the Minister of Religion No. 3 August 11, 1950. In the study of Islamic education, there is a classification (taqsîm) of knowledge, the first is al-'ulum al-diniyyah (religious sciences) which is called religious science and the second is general science or general sciences. In essence, Islam has never recognized the dichotomy of science (tafriqh), Islam only recognizes classification (taqsîm) based on the sequence and stages of learning, starting from fardlu 'ain and fardlu kifayah. The scholars and figures have formulated solutions starting from the regulatory aspect as stated in the joint regulation of the Minister of Religion and the Minister of Education, several other strengthening regulations through the 2003 National Education System formulation and the Higher Education Regulation, or in the form of ideas and ideas such as the tree of knowledge scheme, integration, integration. -interconnection and Naquib Al-Attas' ideal idea of ​​Islamization.